1998
DOI: 10.1111/j.1749-6632.1998.tb11182.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Toxicity in the Lung and Neuronal Cells: Prevention or Attenuation by VIP and PACAP

Abstract: VIP, which has been demonstrated to reduce or prevent oxidant injury in the lungs and other organs, is shown here to protect against excitotoxic injury of the lung and excitotoxic death of cortical neuronal cells in primary culture. Glutamate killing of neuron-like PC-12 cells, attributable to oxidant stress rather that to excitotoxicity, is also reduced or prevented by VIP and by the closely related peptide PACAP. The exact mechanisms of this protection remain to be determined, but appear to include antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…VIP protects the neurons against death from the electric impulse blockade by tetrodotoxin (Kaiser and Lipton, 1990), neuronal growth factor deprivation (Tanaka and Koike, 1994), N-methyl-D-aspartate (NMDA)-mediated glutamate toxicity (Said et al, 1998), HIV glycoprotein 120 toxicity (Brenneman et al, 1988), dopamine toxicity (Offen et al, 2000), or amyloid-␤ peptide toxicity (Gozes et al, 1996Said, 2000). VIP exerts these trophic influences by inducing the astrocytes to release the activity-dependent neurotrophic factor (Brenneman et al, 1999).…”
Section: Functional Implications Of the Localization Of Vip/pacap Recmentioning
confidence: 98%
“…VIP protects the neurons against death from the electric impulse blockade by tetrodotoxin (Kaiser and Lipton, 1990), neuronal growth factor deprivation (Tanaka and Koike, 1994), N-methyl-D-aspartate (NMDA)-mediated glutamate toxicity (Said et al, 1998), HIV glycoprotein 120 toxicity (Brenneman et al, 1988), dopamine toxicity (Offen et al, 2000), or amyloid-␤ peptide toxicity (Gozes et al, 1996Said, 2000). VIP exerts these trophic influences by inducing the astrocytes to release the activity-dependent neurotrophic factor (Brenneman et al, 1999).…”
Section: Functional Implications Of the Localization Of Vip/pacap Recmentioning
confidence: 98%
“…8). In agreement with their anti-inflammatory role, VIP and PACAP were recently reported to inhibit the in vitro and in vivo production of proinflammatory cytokines such as IL-6 and TNF␣ (11)(12)(13), to reduce the expression of the inducible nitric-oxide synthase (14), to enhance the production of the anti-inflammatory cytokine IL-10 (15), to protect mice from endotoxic shock presumably through the inhibition of endogenous TNF␣ and of other inflammatory mediators (16), and to act as survival factors against tissue injury of lung and neuronal cells (17)(18)(19). Furthermore, we and others have recently demonstrated that VIP and PACAP inhibit IL-12 production in endotoxin-stimulated peritoneal macrophages (20 -22), with a subsequent inhibitory effect on IFN␥ synthesis by T cells (22).…”
mentioning
confidence: 99%
“…Also, a synthetic VIP analogue ((Arg 15,20,21 Leu 17 )-VIP-Gly-Lys-Arg-NH 2 ) inhibited neutrophil recruitment in rat airways in vivo [61]. Other possible mechanisms of action include the reduction or prevention of oxidant injury through neutralization of free radicals [108,109]. Finally, there is data suggesting that VIP can modulate the release of T lymphocyte cytokines in the mucosa [110].…”
Section: Asthmamentioning
confidence: 98%